Hydrazides in the reaction with hydroxypyrrolines: less nucleophilicity – more diversity - Shabalin, Dmitrii A.; Ivanova, Evgeniya E.; Ushakov, Igor A.; Schmidt, Elena Yu.; Trofimov, Boris A. (Beilstein Journal of Organic Chemistry, 2021)
Expedient protocols for the synthesis of three types of highly functionalized azaheterocyclic scaffolds (dihydropyridazines, tetrahydropyridazines, and partially saturated tricyclic systems) from readily available hydroxypyrrolines and hydrazides are described. The directions of the transformation of a common initial intermediate, namely a Brønsted acid-activated hydroxypyrroline, depend on the reaction conditions and the structure of the hydrazides.
Keywords: hydrazides; pyridazines; pyrrolines; recyclization; ring expansion